Magnetic and transport properties of Sb2Te3 doped with high concentration of Cr. (5th September 2017) - Gupta, Sachin; Kanai, Shun; Matsukura, Fumihiro; Ohno, Hideo
Abstract: We report on the molecular beam epitaxy and properties of a magnetic topological insulator (TI): Cr-doped Sb2 Te3 . Composition analysis reveals that Cr replaces Sb, and X-ray diffraction confirms that a single-phase textured crystal structure can be obtained for (Cr x Sb1− x )2 Te3 with x up to 0.44. A further increase in x results in phase separation or precipitates in the material. The Curie temperature T C increases with x up to 0.44 and reaches 250 K, which is the highest T C observed thus far in magnetically doped TIs.